2017
DOI: 10.22159/ajpcr.2017.v10i9.19453
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Good Glycemic Control Among Type Ii Diabetes Patients in Palestine

Abstract: Objectives: The aim of this study is to assess glycemic control and its relationship with patient characteristics, health-care system factors, and self-care management in type II diabetes patients. Methods:A retrospective cross-sectional study was conducted among 330 type II diabetes patients who met the inclusion criteria and whose medical records covered a period of 1 year. Data concerning patient characteristics, health-care system factors, self-care management, and available last reading of hemoglobin A1c … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
0
5
1
Order By: Relevance
“…Their results contradict previous findings because of differences in the demographics of the studied populations, especially in terms of the age distribution (Radwan et al, 2018). Higher percentages of participants were of older age in the Palestinian samples than in other study groups, with 34% of participants >61 years (Radwan et al, 2018) and more than 50% ≥58 years (Mosleh et al, 2017). The second demographic aspect examined was gender.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…Their results contradict previous findings because of differences in the demographics of the studied populations, especially in terms of the age distribution (Radwan et al, 2018). Higher percentages of participants were of older age in the Palestinian samples than in other study groups, with 34% of participants >61 years (Radwan et al, 2018) and more than 50% ≥58 years (Mosleh et al, 2017). The second demographic aspect examined was gender.…”
Section: Discussioncontrasting
confidence: 83%
“…Their results contradict previous findings because of differences in the demographics of the studied populations, especially in terms of the age distribution (Radwan et al, 2018). Higher percentages of participants were of older age in the Palestinian samples than in other study groups, with 34% of participants >61 years (Radwan et al, 2018) and more than 50% ≥58 years (Mosleh et al, 2017). However, studies from Aldossari et al (2019), Nemeh et al (2011), and Saghir et al (2019) providing data from Saudi Arabia, Jordan, and other locations, respectively, did not show a significant inverse correlation between age and HbA1c.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…It buttresses the report of some other studies where increment of age, particularly above 40 years, was associated with an elevated level of HbA 1c that is having poor glycemic control (Tokuyama et al, 2008;Harrabi et al, 2014;Camara et al, 2015;Oladoyinbo et al, 2019). But, there are also some studies that found negative or no significant association between poor glycemic control and age of the participants (Adham et al, 2010;Khattab et al, 2010;Yazidi et al, 2016;Mosleh et al, 2017;Tekalegn et al, 2018). The possible explanation for the poor glycemic control among the participants of the middle-age group found in our study might be for their reluctance about the disease control, self-care and adherence to treatment recommendations because of their busy life schedule and/or less interaction with health-care providers.…”
Section: Glycemic Controlmentioning
confidence: 70%
“…This low level of glycemic control has been similarly shown in some other studies. In Palestine, for example, about 83.3% had low glycemic control (Mosleh et al, 2017); in Ethiopia, about 81.7% (Angamo et al, 2013); and about 80% (Tekalegn et al, 2018); in Saudi Arabia, about 78% (Harrabi et al, 2014); in Malaysia, about 77% (Ahmad et al, 2014); and in Venezuela, about 76% (Moreira et al, 2010) of the patients had poor glycemic control.…”
Section: Discussionmentioning
confidence: 98%